Pengaruh Penggunaan Youtube Sebagai Media Pembelajaran Terhadap Hasil Belajar Berbicara Bahasa Inggris Siswa Di Kelas X MA Nurul Falah Air Molek : The effect of YouTube as learning media toward student's speaking achievement at class X of MA Nurul Falah - oktaviani, serli; Syaftinentias, Widi; Wahyuningsih , Destri (Jurnal Riset Guru Indonesia, 2025)
This research aims to investigate the effect of YouTube as a learning media on students’ speaking achievement in Class X of MA Nurul Falah Air Molek. Using an experimental method with pre-test and post-test design, two classes were selected: one as the control group and the other as the experimental group. The experimental group was taught using YouTube-based materials, while the control group received conventional instruction. The results show a significant improvement in the speaking scores of the experimental group compared to the control group. This indicates that YouTube is an effective tool to enhance students’ English speaking skills.